Determining of Climatic Parameters Using CFD in Different Window Span in Naturally Ventilated Greenhouses - Ahmet Tezcan; Kenan Buyuktas (Journal of Basic & Applied Sciences, 2021)
The aim of this study was to compare with the measured inner air temperature and relative humidity values and the simulated values determined with Computational Fluid Dynamics (CFD) in the naturally ventilated gable-roofed single glass greenhouse located North-South direction, having 45o and 90° window spans and under no cultivation. The measured values were recorded every 2 hours from 8 am to 18 pm using the relative humidity and air temperature sensors placed in 7 different locations. Measurements were made in case of the 45° and 90° window span openness. For CFD simulations, the SolidWorks 2011 software was used. The values of air temperature and relative humidity inside the greenhouse were simulated depending on the outside ambient conditions and structural and physical properties of greenhouse. Then, the measured values were compared with the simulated values and error rate for each sensors were determined. As a result, it was determined minimum error rates of the measured and simulated air temperature and relative humidity in greenhouses is 4.8% and 4.7%, respectively. The study showed that the CFD can be used as a powerful tool for determining inner climatic factors in naturally ventilated greenhouses.